Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Justice Donald Franson, Sr. and Hastings College of the Law Dean Mary Kay Kane Luncheon held at the Downtown Club